Media Sosial Sebagai Strategi Pencegahan Tawuran Pelajar - Monica Margaret; Awaluddin Marifatullah (Universitas Persada Indonesia YAI, 2023)
This study discusses about student brawls which are a bad tradition that has been passed downuntil now unresolved, the role of alumni is very influential on the new generation in the school. Inthe era of technological development, technology is developing very rapidly so that it makes iteasier for users to express themselves, both expressing in a positive and negative direction. Studentbrawls that follow technological developments are now widespread in social media circles whichcause violent content to emerge. The role of alumni and the community outside the police unit whowork together in preventing these brawls by utilizing social media as a forum for preventive actionand stop brawl campaigns. This research was conducted with a qualitative approach anddescriptive method using primary data obtained from interviews with students about the stop brawlcampaign using Social Control Theory (Social Bond Theory) along with Social Crime PreventionTheory so as to suppress the intention for these consumers not to commit crimes, brawl withprevention carried out from the elements of society